2009
DOI: 10.1128/jvi.02441-08
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical, Biophysical, and Mutational Analyses of Subunit Interactions of the Human Cytomegalovirus Nuclear Egress Complex

Abstract: Nuclear egress, the trafficking of herpesvirus nucleocapsids from the nucleus to the cytoplasm, involves two conserved viral proteins that form a complex at the nuclear envelope, referred to as the nuclear egress complex. In human cytomegalovirus, these two proteins are called UL50 and UL53. To study UL50 and UL53 in molecular detail, these proteins were expressed in bacteria and purified. To obtain highly expressed, pure proteins, it was necessary to truncate both constructs based on sequence conservation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
97
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(115 citation statements)
references
References 25 publications
(52 reference statements)
18
97
0
Order By: Relevance
“…Specific Structural Determinants Accomplish a Tight Interlocking of the pUL50-pUL53 Heterodimer-pUL50 and pUL53 readily form a complex when mixed in solution (38). The crystal structure reveals the hallmarks of the interaction and at the same time corroborates previous findings from mutagenesis experiments (14,38).…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…Specific Structural Determinants Accomplish a Tight Interlocking of the pUL50-pUL53 Heterodimer-pUL50 and pUL53 readily form a complex when mixed in solution (38). The crystal structure reveals the hallmarks of the interaction and at the same time corroborates previous findings from mutagenesis experiments (14,38).…”
Section: Resultssupporting
confidence: 77%
“…The crystal structure reveals the hallmarks of the interaction and at the same time corroborates previous findings from mutagenesis experiments (14,38). In the pUL50-pUL53 complex, each protein contributes as much as 1880 Å 2 of solvent-accessible surface area to the protein interface.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…Previous studies indicated that the interaction interface on M53 and UL53 includes a predicted amphipathic helical segment interrupted by a proline comprising residues 60-82 (Fig. S4A) and requires both hydrophobic residues and charged residues within this predicted helix (17,30). We speculate that at least part of this helical segment fits within the groove in such a way as to allow burying of bulky hydrophobic sidechains present in the peptide (Fig.…”
Section: Significancementioning
confidence: 99%
“…To gain insight into this interaction, we hypothesized that the strong sequence conservation between both subunits of the HCMV and MCMV NECs would allow M50 to bind a peptide derived from a region of HCMV UL53 that was previously shown to be important for heterodimer formation (Figs. S1B and S4A) (30). We titrated this synthetic UL53 peptide into 15 N-labeled M50 (1-168) and monitored the binding using a series of 1 H-15 N heteronuclear single-quantum coherence (HSQC) experiments.…”
Section: Significancementioning
confidence: 99%